Associations of discrimination and physical activity with social pain sensitivity and a moderating effect of gender in young adults - Masataka Umeda; Youngdeok Kim; Se-Woong Park; Eunhee Chung (PLoS ONE, 2025)
Objective Social pain can be evoked by social rejection. Discrimination is a type of social rejection based on attributes of individuals and linked to pain and hyperalgesia, whereas physical activity (PA) is a healthful behavior that is linked to pain relief and hypoalgesia. However, associations of discrimination and PA with social pain sensitivity is currently unknown. Gender differences in social pain sensitivity exist, but it is unclear if gender moderates the associations of discrimination and PA with social pain sensitivity. The primary aim of this study was to examine the associations of perceived discrimination and PA with social pain sensitivity, and the secondary aim was to explore the moderating effect of gender. Methods A total of 172 young adults completed 1) Brief Fear of Negative Evaluation Scale (BFNES) and Social Pain Questionnaire (SPQ) to evaluate social pain sensitivity, 2) Everyday Discrimination Scale (EDS) to quantify perceived discrimination, and 3) PA survey. Results The EDS scores were associated with both BFNES and SPQ scores in the total sample (BFNES: Β = 0.16, p = 0.028 & SPQ: Β = 0.25, p < 0.001). The EDS scores were associated with both BFNES and SPQ scores in men (BFNES: Β = 0.28, p = 0.014 & SPQ: Β = 0.46, p < 0.001), but not in women (BFNES: Β = 0.11, p = 0.221 & SPQ: Β = 0.10, p = 0.239). PA levels were associated with the SPQ scores (Β = −0.34, p = 0.024) in the total sample, but when stratified by gender, the significant association disappeared for both men and women (men: Β = −0.49, p = 0.065 & women: Β = −0.33, p = 0.082). Conclusions Both perceived discrimination and PA levels were associated with social pain sensitivity. Gender moderated the association between perceived discrimination and social pain sensitivity.